Physical Activity Monitoring in Portugal: Looking for a Surveillance System (Baltic Journal of Sport and Health Sciences, 2026)
Purpose: This study aimed to analyse the state-of-play of physical activity (PA) surveillance in Portugal. Studies assessing population-level PA were evaluated for their potential to be considered PA surveillance systems (SS) based on their compliance with defined quality criteria.Methods: A literature search was conducted to identify studies assessing population-level PA in Portugal. Ten quality criteria for PA SS were defined: 1) use of a scientifically validated instrument; 2) repeated measurements over time; 3) assessment of all age groups across the lifespan; 4) use of a nationally representative sample; 5) combination of self-reported data (questionnaires) with objective measures (accelerometers); 6) assessment of PA contexts; 7) collection of sedentary behaviour data; 8) use of the World Health Organization’s cut-off points for sufficient PA levels; 9) interpretation of results based on sociodemographic variables; and 10) public accessibility and dissemination of results. Identified studies were evaluated for compliance with these criteria.Results: Ten studies were identified and assessed. None of the studies met all quality criteria. Criteria 1) was met by 90% of the studies; 2) 80%; 3) 0%; 4) 50%; 5) 10%; 6) 80%; 7) 100%; 8) 30%; 9) 100%; 10) 100%.Conclusion: A considerable number of studies assess PA levels in the Portuguese population, some within similar contexts but using different methodologies, leading to inconsistent and difficult-to-compare results. The quality assessment framework used may be applied in other countries to evaluate their data sources. If applied across countries, this framework could support the harmonisation of surveillance practices and enhance comparability, while also contributing to broader international monitoring efforts. In both Portugal and internationally, addressing the identified gaps (specially criteria 3, 4, 5, and 8) is essential to improve PA monitoring. These findings highlight the urgent need for a unified SS to monitor PA in Portugal, enabling more effective evaluation of health promotion policies.Support/Funding Source: FCT – Fundação para a Ciência e a Tecnologia [Foundation for Science and Technology], UIDB/04750/2020 and LA/P/0064/2020.